2020
DOI: 10.1177/0963689720962460
|View full text |Cite
|
Sign up to set email alerts
|

miR-19 Promotes Cell Proliferation, Invasion, Migration, and EMT by Inhibiting SPRED2-mediated Autophagy in Osteosarcoma Cells

Abstract: Osteosarcoma is an aggressive malignancy with rapid development and poor prognosis. microRNA-19 (miR-19) plays an important role in several biological processes. Sprouty-related EVH1 domain protein 2 (SPRED2) is a suppressor of extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) signaling to inhibit tumor development and progression by promoting autophagy. In this study, we investigated the roles of miR-19, SPRED2, and autophagy in osteosarcoma. We detected the expression of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…These results indicate that the upregulation of miR‐19b may be responsible for stemness maintenance and radioresistance in CRC. Consistently, miR‐19 promoted cell proliferation, invasion, and migration in osteosarcoma cells 19 . More relevantly, overexpression of miR‐19b was associated with metastasis and poor prognosis in patients with CRC 20 .…”
Section: Discussionmentioning
confidence: 74%
“…These results indicate that the upregulation of miR‐19b may be responsible for stemness maintenance and radioresistance in CRC. Consistently, miR‐19 promoted cell proliferation, invasion, and migration in osteosarcoma cells 19 . More relevantly, overexpression of miR‐19b was associated with metastasis and poor prognosis in patients with CRC 20 .…”
Section: Discussionmentioning
confidence: 74%
“…By downregulating the expression of PIK3R5 and regulating the AKT/mTOR signaling pathway, miR-210-5p promoted the cellular process called epithelial–mesenchymal transition (EMT), which is characterized by cells progressively losing epithelial features and acquiring mesenchymal properties, peculiar aspects of invasive and metastatic cells [ 43 ]. An oncogenic miRNA, member of the miR-17-92 cluster, was upregulated in OS cells and negatively regulated SPRED2, thus promoting the malignant transformation of osteosarcoma cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported that TGF-β can promote tumor metastasis by inducing EMT [24][25][26]. Although osteosarcoma is derived from mesenchymal cells, a large number of recent studies [27][28][29] have found that EMT also plays a key role in the metastasis of osteosarcoma. Whether EMT process involved in VCP-mediated metastasis of osteosarcoma is remained unknown.…”
Section: Introductionmentioning
confidence: 99%